First report of Raoiella indica (Acari: Tenuipalpidae) in southeastern Brazil - Oliveira, Daniel Chiaradia; Prado, Evandro Pereira [UNESP]; Moraes, Gilberto Jose de; Fidelis de Morais, Elisangela Gomes; Chagas, Edvan Alves; Correa Gondim, Manoel Guedes; Navia, Denise (Florida Entomological Soc, 2016)
The red palm mite, Raoiella indica Hirst (Acari: Tenuipalpidae), was found for the first time in the urban area of Dracena, state of Sao Paulo, southeastern Brazil, in May 2015, on Cocos nucifera L., Phoenix roebelenii O'Brien, and Rhapis excelsa (Thunb.) A. Henry (Arecales: Arecaceae). Raoiella indica was first reported in Brazil in the state of Roraima, in 2009, and subsequently found in Manaus, Amazonas State, in 2011. Discovery of R. indica in Dracena, about 2,300 km southeast of Manaus, represents a major range expansion, suggesting that its arrival in northeastern Brazil is imminent, where hosts and climate conditions are favorable to its development. Coconut is an important crop in this region of Brazil and may incur major loss.
Keywords: Arecaceae; red palm mite; quarantine pest; Sao Paulo; plant protection